Surgical Correction of Postoperative Ventral Hernias After Non-Tensioned Hernioalloplasty (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The treatment of 26 patients with postoperative ventral hernias after non-tensioned hernioalloplasty has been analysed. Partial recurrence of hernias along the lower and upper contours of fixation of the prosthesis to the tissues as well as hernias through the defects of the damaged prosthesis are characteristic for the non-tensioned prosthetic method of plastic surgery. Mature connective tissue with fibrous transformation, diffuse focal lipomatosis and moderate lymphocytic infiltration are characteristic after non-tensioned combined methods of plasty. The above factors in conjunction with increased intra-abdominal pressure are the basis for the formation of hernia recurrence. In surgical treatment of postoperative ventral hernias it is recommended to use improved methods of hernioalloplasty - "on lay" without suturing the defect with implantation of endoprosthesis with U-shaped sutures (at W1-W2) or "on lay+sub lay" with creation of duplicate prosthesis (at W3-W4). The proposed improved methods of non-tensioned prosthetic plasty in patients with recurrent ventral hernias allowed to improve significantly the results of treatment by reducing the recurrence of the disease from 15% to 3.8%.